Environmental Change, Migration, and Conflict in Africa: A Critical Examination of the Interconnections. (December 2017) - Freeman, Laura
How should we understand the interconnections between environmental change, migration, and conflict in Africa? Should the rise of Islamic terrorism and Boko Haram in northeast Nigeria be directly linked to the drying of Lake Chad? Should cattle raiding in Kenya be seen as a result of drought across East Africa? Does the constrained migration of the pastoral Tuareg in the Sahel causally connect to desertification and their rebellion against governmental forces? Despite the compelling and often persuasive case for directly connecting environmental change to migration and conflict, there is a growing agreement in both the environment-migration and climate-conflict spheres that intervening variables determine if and how environmental change causes population movements and political violence. This article presents a case for migration as an intermediary and bidirectional causal variable. The article argues that close attention needs to be paid to local-level manifestations of conflict and (mal)adaptive forms of migration to understand the potential propensity of environmental change to lead to conflict in Africa.